As Folias de Reis: uma leitura da cultura mineira mediada pela comunicação - Marinho, Neide Aparecida (2012)
The object of this study is the Folia Estrela do Norte , from Juiz de Fora, Minas Gerais/Brazil, from 2010 to 2011. Our main objective is to place the research of Folia de Reis , a Brazilian popular festival, in the context of recent communication studies. Through the symbols constituents of the Folias , re-investigate the meanings and usages elaborated within the communities that produce and reproduce the festivals. We seek primarily to understand how this popular ritual dialogues with the mass media. To this, we investigated the communicational aspects of the rituals. Theirs "mythologies" survive through (and despite) the industrial and digital society. Our problem: how the rituals of the Folias de Reis dialogue with the mass media? The research has shown that, in mixed cultures, flexible and mobile, the popular and the massive, the oral and the written, the open and the closed, the center and the periphery they all dialogue in tension, incorporating outside elements and breaking oppositions. We analyzed the dialogue between popular and massive, a major issue in cultures such as ours, constantly reworked from the incorporation of others, forming new cultural texts, in network and mosaic. Our main theoretical basis is the communication studies of mediations between popular culture and mass culture; how the popular and folkloric manifestations are incorporated and reworked by the cultural industry that, at the same time, provides projections and recreations? Another point is the palhaços , important characters of the Folia , and their masks that, full of representativeness, disguise, frighten and hide, allowing the man to present his "being and not being" condition. In these masks are present the legendary, the sacred and the profane, in images of grotesque that appropriate themselves of a baroque which is translated into exuberant costumes, mapping the territory of the mixed culture. Thus we find the current masking that, in a symbolic appropriation, shows the daily experiences that leave "marks", or "social masks", creating opportunities for camouflage. Contribute to our theoretical basis intellectuals of mediations theories, such as Néstor García Canclini and Jesús Martín-Barbero. From the mestizaje theories, we can mention Amalio Pinheiro, Serge Gruzinski, Peter Burke, Yuri Lotman and Laplantine